SYSTEMATIC LITERATURE REVIEW : KESEJAHTERAAN SUBJEKTIF PADA GURU - Prabasari Nuswantari, Putri; Anugerah Izzati, Umi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Subjective well-being for teachers is essential in improving the quality of education for students. Therefore, enhancing subjective well-being, supported by other contributing factors, becomes crucial. This article aims to explore the significant role of teachers’ subjective well-being. The research employs a descriptive research design with a Systematic Literature Review (SLR) approach. This study adopts a systematic review of literature (SLR), utilizing secondary data sourced from previously published and publicly accessible scientific articles. The databases used include Google Scholar, ScienceDirect, ResearchGate, and several others, resulting in the selection of 12 relevant articles. Based on the analyzed data, the findings indicate that teachers with high levels of subjective well-being tend to be more motivated, creative, and committed to their profession, ultimately contributing to overall educational success. Therefore, maintaining and enhancing teachers’ subjective well-being is not only an individual concern but also a collective responsibility within the educational system. ABSTRAK Kesejahteraan subjektif bagi guru sangat diperlukan guna meningkatkan kualitas pendidikan bagi peserta didik, dengan itu pentingnya peningkatan kesejahteraan subjektif dibantu dengan faktor lainnya, artikel ini bertujuan untuk mengetahui peran penting kesejahteraan subjektif bagi guru. Pendekatan penelitian yang digunakan adalah desain penelitian deskriptif dengan pendekatan systematic literature review (SLR). Penelitian ini mengadopsi tinjauan literatur sistematis (SLR). Penelitian ini Memanfaatkan data sekunder yang bersumber dari artikel ilmiah yang telah di publikasikan dan dapat diakses secara online, database tersebut berupa Google Scholars, ScienceDirect, ResearchGate, dan beberapa database lainnya dan mendapati 12 artikel. Berdasarkan data yang telah dilakukan, didapatkan hasil bahwa guru yang memiliki kesejahteraan subjektif tinggi cenderung lebih termotivasi, kreatif, dan berkomitmen terhadap profesinya, yang pada akhirnya berkontribusi pada keberhasilan pendidikan secara menyeluruh. Oleh karena itu, menjaga dan meningkatkan kesejahteraan subjektif guru bukan hanya menjadi kepentingan individu, tetapi juga merupakan tanggung jawab kolektif dalam sistem pendidikan.